1991
DOI: 10.1111/j.1532-950x.1991.tb01262.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Injectable Anesthetic Combinations in Horses

Abstract: Six combinations of injectable anesthetic agents were administered to six adult horses in a Latin square design. The drug combinations were xylazine-ketamine, xylazine-butorphanol-ketamine, xylazine-tiletamine-zolazepam, xylazine-butorphanol-tiletamine-zolazepam, detomidine-ketamine, and detomidine-butorphanol-ketamine. Measured variables were heart rate, respiratory rate, systolic blood pressure, arterial pH (pHa), PaCO2, PaO2, recumbency time, and number of attempts necessary to stand. Quality of induction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 3 publications
4
58
1
2
Order By: Relevance
“…These effects, however, sometimes result in prolonged recovery and there is no readily available antagonist, or reversal agent (Matthews et al 1991;Muir et al 2000). The solubility of the concentrated ketamine preparations is insufficient to allow dosing darts with a capacity restricted to 3ml.…”
mentioning
confidence: 99%
“…These effects, however, sometimes result in prolonged recovery and there is no readily available antagonist, or reversal agent (Matthews et al 1991;Muir et al 2000). The solubility of the concentrated ketamine preparations is insufficient to allow dosing darts with a capacity restricted to 3ml.…”
mentioning
confidence: 99%
“…In the present study, the clinical anaesthesia parameters resulting from the anaesthesia protocol applied (Table 3) was found to be in compliance with the findings of the studies referred to above. In several studies 1,3,8,[10][11][12][13][14] , it has been reported that, in horses, tiletamine-zolazepam anaesthesia, and in particular anaesthesia prolonged by the administration of sustaining doses, tend to be problematic due to the continuous attempts of the animals to stand up, the standing position of the animals being unsafe owing to ataxia, and consequential falls of the animals. These problems have been indicated to result from the half life elimination time (t ½) of zolazepam from the organism taking a longer time than that of xylazine and tiletamine, thereby, leading to longer muscle relaxation and ataxia during recovery from anaesthesia.…”
Section: Bidwellmentioning
confidence: 99%
“…In previous studies carried out in horses and foals by administering different doses of the anaesthetic combination of xylazine-tiletamine-zolazepam for the induction of general anaesthesia 5,8,[10][11][12][13][14] , anaesthesia induction time was reported to range between 34-75 sec, the duration of anaesthesia between 22.5-35.7 min, and the period of regaining standing position (standing time) between 30-50 min. Furthermore, it has been indicated that, if required, the duration of anaesthesia could be prolonged by administering half or one-third of the initial doses of the anaesthetics used for sustainment, yet, in such cases, complications such as serious hypoxaemia, myositis and delayed recovery from anaesthesia could be encountered as a result of cardiovascular/pulmonary depression 1,3,4,6,11,27 .…”
Section: Bidwellmentioning
confidence: 99%
See 2 more Smart Citations